Early Post operative Pain Management and Early Extubation after Off-pump Coronary Artery Bypass Graft Surgery is better managed with Thoracic Epidural Analgesia - Mandal, Naresh Chandra; Hossain, Md Fidah; Dey, Nirmal Kanti; Sarkar, Md Motiur Rahman; Mamun, Abdullah Al; Arif, Ashfaque; Hakim, Mohammad Enamul (Cardiovascular Journal, 2017)
Background: Off-pump coronary artery bypass (OPCAB) graft surgery is the commonest operation worldwide. Sternotomy, pleurotomy with opening of the pleural space, harvesting of internal mammary artery may lead to severe post-operative pain. Thoracic epidural analgesia (TEA) may reduced significant post-operative pain & allow the patient early extubation. Methods: A total of 60 patients with ischaemic heart disease (IHD) were included in the study who were admitted in the Department of Cardiac Surgery in NICVD, Dhaka from July 2006 to June 2008 & underwent off-pump coronary artery bypass (OPCAB) graft surgery. Out of the total 60 patients, 30 were in the group-A receiving thoracic epidural analgesia along with general anaesthesia and the rest 30 were in the group-B receiving general anaesthesia alone. Results: Patients in the epidural group had significantly less pain on the operative day and for the next 2 days. Total ventilation time in hours in Group-A was 6.4 + 1.0 and in Group-B was 10.1 +1.8 hours respectively. Postoperative X-ray chest revealed significant pulmonary complication in Group- B than Group-A. There were no complications related to epidural haematoma and no permanent neurological squeal. Conclusion: Thoracic epidural analgesia reduced significant post-operative pain and improvement in pulmonary function and early extubation. Cardiovasc. j. 2017; 9(2): 142-146